A global approach to the gender gap in mathematical, computing and natural sciences : how to measure it, how to reduce it? - Chiu, Mei-Hung; Roy, Marie-Françoise; Mihaljević, Helena; Gledhill, Irvy M.A.; Ivie, Rachel; Ponce-Dawson, Silvina (South African Journal of Science, 2019)
The participation of women in many fields of science remains a subject of concern worldwide. In this Commentary, we describe one of three collaborative projects – the Gender Gap project – funded by the International Science Council (ISC) and the 11 partners of the project. This project is the only one of the three that addresses an issue of such relevance for society. The objectives of the project are to provide evidence on which interventions can be based, and to make available material on best practice that has been proven by test. The project includes a joint global survey and a bibliometric analysis, both of which have an emphasis on comparing and contrasting results from less developed countries and from more developed countries.